Understanding and Implementation of Syariah in the Midst of Urban Modernity - Mila Marshela; Nurjaya Nurjaya; Sumarta Sumarta; Kusyana Kusyana; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the fundamental framework of Islamic teachings, with a particular focus on the concept of Shariah and its integral role in the lives of Muslims. The research employs a qualitative library review method, drawing upon various Islamic texts and scholarly interpretations. The main findings indicate that Shariah constitutes a comprehensive set of divine laws ordained by Allah to guide human beings in their relationships with God, fellow humans, and the natural environment. A proper understanding and implementation of Shariah are essential for Muslims to live in accordance with Islamic principles. The study further highlights that inadequate understanding of Shariah may lead to moral and spiritual decline, as individuals may misinterpret or neglect its teachings. This study concludes by emphasizing the importance of integrating Shariah into daily life to ensure spiritual and moral well-being in line with Islamic values. The implications suggest that disseminating accurate knowledge of Shariah is crucial to prevent disorientation in religious and social practices among Muslims. It also underscores the need for improved educational programs on Shariah principles. The originality of this research lies in its comprehensive emphasis on Shariah as a fundamental pillar that not only governs acts of worship but also shapes all dimensions of Muslim life, including social interactions and environmental ethics, while identifying the potential negative impacts arising from its misinterpretation or lack of understanding.